Strategic cultural interventions in systems science - Examining the prospects for the further development of methodological complementarism - Brocklesby, John (School of Management Working Papers, 1994)
This paper contemplates the prospect of the complementary use of hard, soft, and critical systems methodologies, becoming a more established practice among the diverse company of operational researchers and management scientists in academe, commerce and Government, who have been trained in systems thinking and apply its language and concepts in dealing with organisational problems. The paper takes the line that any individual's orientation towards methodology is predicated upon distinctive meanings, many of which are constructed socially in particular cultural settings. Because of this, any attempt to alter the predominant methodological bearing of a complete discipline or field of enquiry has to grapple with the problems involved in both imparting to members new technical knowledge and competences, and creating new sets of meanings. Thus I argue here that attempts to inculcate a complementarist approach in systems science amounts to a form of cultural visioning. Creating a vision of complementarism as integral to the development of the discipline of systems is seen here as a strategic intervention in the culture of systems science. In the paper, cultural transitioning from the existing specialisations of systems science towards methodological complementarism is conceptualised as requiring members to undergo a form of organisational learning. This is contingent upon the existence of a broad set of propitious circumstances; the existence of which is questionable in this particular case. Although the idea of complementarism is the principal focus of the paper, much of the argument applies equally to other attempts to deliberately intervene in the culture of systems science